Mutations in FEZF1 Cause Kallmann Syndrome - Kotan, L. Damla; Hutchins, B. Ian; Ozkan, Yusuf; Demire, Fatma; Stoner, Hudson; Cheng, Paul J.; Topaloglu, A. Kemal (Cell Press, 2014)
Gonadotropin-releasing hormone (GnRH) neurons originate outside the CNS in the olfactory placode and migrate into the CNS, where they become integral components of the hypothalamic-pituitary-gonadal (HPG) axis. Disruption of this migration results in Kallmann syndrome (KS), which is characterized by anosmia and pubertal failure due to hypogonadotropic hypogonadism. Using candidate-gene screening, autozygosity mapping, and whole-exome sequencing in a cohort of 30 individuals with KS, we searched for genes newly associated with KS. We identified homozygous loss-of-function mutations in FEZF1 in two independent consanguineous families each with two affected siblings. The FEZF1 product is known to enable axons of olfactory receptor neurons (ORNs) to penetrate the CNS basal lamina in mice. Because a subset of axons in these tracks is the migratory pathway for GnRH neurons, in FEZF1 deficiency, GnRH neurons also fail to enter the brain. These results indicate that FEZF1 is required for establishment of the central component of the HPG axis in humans.
Keywords: Idiopathic Hypogonadotropic Hypogonadism; Gonadotropin-Releasing-Hormone; of-Function Mutations; Finger Genes Fezf1; Olfactory System; Protein; Identification; Deficiency; Adhesion; Fgfr1